First description and validation of a new method for estimating aortic stenosis burden and predicting the functional response to TAVI - de la Torre Hernandez, Jose M.; Veiga Fernandez, Gabriela; Ben-Assa, Eyal; Iribarren, Julia; Sainz Laso, Fermin; Lee, Dae-Hyun; Ruisanchez Villar, Cristina; Lerena, Piedad; Garcia Camarero, Tamara; Iribarren Sarrias, Jose L.; Cuesta Cosgaya, Jose M.; Maza Fernandez, Maria E.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Up to one-fifth of patients continue to have poor quality of life after transcatheter aortic valve implantation (TAVI), with an additional similar proportion not surviving 1 year after the procedure. We aimed to assess the value of a new method based on an integrated analysis of left ventricular outflow tract flow velocity and aortic pressure to predict objective functional improvement and prognosis after TAVI. Methods In a cohort of consecutive patients undergoing TAVI, flow velocity–pressure integrated analysis was obtained from simultaneous pressure recordings in the ascending aorta and flow velocity recordings in the left ventricular outflow tract by echocardiography. Objective functional improvement 6 months after TAVI was assessed through changes in a 6-min walk test and NT-proBNP levels. A clinical follow-up was conducted at 2 years. Results Of the 102 patients studied, 82 (80.4%) showed objective functional improvement. The 2-year mortality of these patients was significantly lower (9% vs. 44%, p = 0.001). In multivariate analysis, parameter “(Pressure at Vmax − Pressure at Vo)/Vmax” was found to be an independent predictor for objective improvement. The C-statistic was 0.70 in the overall population and 0.78 in the low-gradient subgroup. All echocardiographic parameters and the valvuloarterial impedance showed a C-statistic of <0.6 for the overall and low-gradient patients. In a validation cohort of 119 patients, the C-statistic was 0.67 for the total cohort and 0.76 for the low-gradient subgroup. Conclusion This new method allows predicting objective functional improvement after TAVI more precisely than the conventional parameters used to assess the severity of aortic stenosis, particularly in low-gradient patients.